2017
DOI: 10.1089/jop.2016.0114
|View full text |Cite
|
Sign up to set email alerts
|

Topical 0.1% Bromfenac Sodium for Intraoperative Miosis Prevention and Prostaglandin E2 Inhibition in Femtosecond Laser-Assisted Cataract Surgery

Abstract: NSAID treatment, when administered before femtosecond laser-assisted cataract surgery, was effective in maintaining intraoperative pupil dilation, preventing miosis, and reducing PGE levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
1
13
0
2
Order By: Relevance
“…Similar result was reported in a study by Cervantes-Coste et al They found prophylactic use of nepafenac 0.1% was more effective in maintaining mydriasis as compared to control group [18]. Another study by Chen H et al showed pre-operative use of topical bromfenac sodium 0.1% in Femtosecond laser assisted cataract surgery was effective in maintaining intraoperative mydriasis as compared to control (placebo) group [19]. Many surgeons are now opting to use NSAID ophthalmic solutions preoperatively and post operatively to reduce intraoperative pain and postoperative inflammation.…”
Section: Original Research Articlesupporting
confidence: 81%
“…Similar result was reported in a study by Cervantes-Coste et al They found prophylactic use of nepafenac 0.1% was more effective in maintaining mydriasis as compared to control group [18]. Another study by Chen H et al showed pre-operative use of topical bromfenac sodium 0.1% in Femtosecond laser assisted cataract surgery was effective in maintaining intraoperative mydriasis as compared to control (placebo) group [19]. Many surgeons are now opting to use NSAID ophthalmic solutions preoperatively and post operatively to reduce intraoperative pain and postoperative inflammation.…”
Section: Original Research Articlesupporting
confidence: 81%
“…Some studies report that topically applied NSAIDs are comparable to topically administered corticosteroids in their ability to control post-cataract inflammation (8-10). The study of Jung et al (11) found that adding NSAIDs (bromfenac 0.1%) to topical steroid reduces intraoperative miosis, postoperative inflammation and macular thickness changes more effectively than postoperative steroid alone (12)(13). Moreover, Coassin et al (14) ISSN 0023-2157 Index 362646…”
Section: Discussionmentioning
confidence: 99%
“…Un recente studio condotto in 60 pazienti sottoposti a chirurgia della cataratta con femto-laser, trattati con bromfenac 0,1% 2 volte al giorno, per 3 giorni prima dell'intervento, ha dimostrato che la variazione del diametro pupillare è inferiore nei pazienti trattati con bromfenac rispetto ai controlli trattati con placebo, con una riduzione significativa dei livelli di PGE2 (Fig. 10) [13].…”
Section: Prevenzione Della Miosi Intraoperatoriaunclassified
“…10-Variazioni del diametro pupillare e livelli medi di PGE2 nell'umore acqueo dei pazienti trattati con bromfenac o placebo. *p < 0,001 (modificata da[13])…”
unclassified